Using chlorofluorocarbons (CFCs) and tritium (3H) to estimate groundwater age and flow velocity in Hohhot Basin, China. Issue 3 (14th January 2013) - Liu, Jun; Chen, Zongyu; Wei, Wen; Zhang, Yilong; Li, Zhenghong; Liu, Fuliang; Guo, Hualiang
Abstract The concentrations of chlorofluorocarbons (CFC‐11, CFC‐12 and CFC‐113) and tritium (3H) content in groundwater were used to date groundwater age, delineate groundwater flow systems and estimate flow velocity in the Hohhot basin. The estimated young groundwater age is fallen in the bracket of 21 ~ 50 a and indicates the presence of two different age profiles and flow systems in the shallow groundwater system. Older age waters occur under the topographically low areas, where the aquifer is double‐layer aquifer system consisting of shallow unconfined‐semi‐confined aquifer and deep confined aquifer. This reflects long flow paths associated with regional flow. Groundwater (range from 21 to 34 years) in the north piedmont and east hilly areas, where the aquifer is a single‐layer aquifer consisting of alluvial fans, are typically younger than those in the low areas. The combination of CFCs dating with hydrogeological information indicates that both local and regional flow systems are present at the basin. The regional groundwater flow mainly flows from the north and east to the southwest, the local groundwater flow system occurs nearby the Hohhot city. The mean regional groundwater flow velocity of the shallow groundwater is estimated about 0.73 km/a. These findings can aid in refining hydrogeological conceptual model of the study area. Copyright © 2012 John Wiley & Sons, Ltd.